2021
DOI: 10.1111/1758-2229.12995
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes and phenotypes of methicillin‐resistant staphylococci isolated from shrimp aquaculture farms

Abstract: Summary The population of methicillin‐resistant (MR) staphylococci in aquatic environment is rarely investigated. Here, we characterized a collection of MR staphylococci recovered from shrimp aquaculture farms (n = 37) in Kerala, India. A total of 261 samples yielded 47 MR isolates (16 S. aureus, 13 S. haemolyticus, 11 S. epidermidis, 3 S. saprophytics and 2 each of S.intermedius and S. kloosii). Multi‐drug resistance was evident in 72.3% of the isolates, with resistance mainly towards erythromycin (78.7%), no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Te PCR confrmed bacterial species were subjected to determination of antibiotic resistance pattern phenotypically using 12 commercial antibiotics from diferent classes and groups such as gentamycin, ampicillin, cefxime, aztreonam, vancomycin, doxycycline, linezolid, erythromycin, chloramphenicol, trimethoprim, levofoxacin, and moxifoxacin following the disc difusion methods [127]. Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Te PCR confrmed bacterial species were subjected to determination of antibiotic resistance pattern phenotypically using 12 commercial antibiotics from diferent classes and groups such as gentamycin, ampicillin, cefxime, aztreonam, vancomycin, doxycycline, linezolid, erythromycin, chloramphenicol, trimethoprim, levofoxacin, and moxifoxacin following the disc difusion methods [127]. Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…7a) indicates the presence of methicillin-resistant S. aureus , 47 as confirmed previously. 80,81 The amplified bands at 643 bp and 577 bp for blaTEM-1 (Fig. 7b) and tetA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We could speculate that in the process of aquaculture, they may be at risk of bacterial infection, especially the Vibrio, since there are many reports of bacterial infection causing a massive economic loss in the aquaculture industry [ 47 , 48 , 49 , 50 ]. Meanwhile, various aquatic animals have suffered from S. aureus infections [ 51 , 52 , 53 , 54 , 55 ]. In the present study, co-incubation assay revealed that recombinant Ct-PGRP-S1 was proven to have antibacterial activity against V. alginolyticus and S. aureus by direct contact, reflecting the importance of Ct-PGRP-S1 in the antibacterial defense of C. tritonis and providing important evidence to suggest that amidase-active PGRPs may function as the key effectors to promote antibacterial response in hosts.…”
Section: Discussionmentioning
confidence: 99%